2020
DOI: 10.7759/cureus.6574
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tumor Size and Malignancy Risk in Hormonally Inactive Adrenal Incidentalomas

Abstract: Introduction Adrenal incidentalomas (AI) are adrenal masses that are discovered during radiological examinations conducted for other reasons. In this study, we focused on the pathological and radiological properties of nonfunctional AI(NFAI) and the association with malignancy risk in our clinical series. Methods A total of 186 patients underwent adrenalectomy between 2010 and 2017; of these, 76 (40.8%) patients with non-functional AI were included in the current study. The radiological and pathologic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
0
7
1
1
Order By: Relevance
“…Adrenal incidentalomas are common endocrine diagnoses which are adrenal masses that are discovered during radiological examination conducted for other reasons [ 190 ]. Often, they should be monitored in terms of radiological characteristics, clinical features, and functional levels.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenal incidentalomas are common endocrine diagnoses which are adrenal masses that are discovered during radiological examination conducted for other reasons [ 190 ]. Often, they should be monitored in terms of radiological characteristics, clinical features, and functional levels.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…On the other hand, ACC accounts for less than 2% of adrenal incidentalomas [ 5 , 193 ]. The rate of malignancy depends on size of the tumour [ 190 ]. A study on 139 operations for adrenal tumour more than 50 mm in diameter showed that the most common tumour (around 25%) were ACC [ 194 ].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…ADX was recommend in the case of AMs more than 3 cm in diameter in young patients, whereas more than 5 cm in older patients [14]. The rate of malignancy of the AMs with diameters of less than 4 cm, 4-6 cm, and more than 6 cm to be 0%, 2.9%, and 13.6% [15]. In our study, histopathologically benign lesions are much smaller than malign lesions, the average diameters of ACC were 98.8 mm.…”
Section: Results Of Clinical and Histopathologic Evaluationsmentioning
confidence: 99%
“…Tissue biopsy was required to rule out the remote possibility of adrenal malignancy. Considering that solid adrenal tumours>6 cm in diameter carry a 25% risk of potential malignancy, cystic adrenal masses carry a much lower malignancy potential of roughly 6% 6 7. Initial fine-needle aspiration biopsy was inconclusive and was repeated with core needle biopsy and cyst aspiration.…”
Section: Discussionmentioning
confidence: 99%